Is VATS lobectomy standard of care for operable non-small cell lung cancer?. (October 2016) - Vannucci, Fernando; Gonzalez-Rivas, Diego
Highlights: VATS lobectomy is safe, feasible and cost-effective procedure. VATS lobectomy offers better post-op quality of life if compared to open surgery. Regarding survival, VATS lobectomy equals to open surgery, if not better. VATS lobectomy should be standard of care in early stage non-small cell lung cancer. VATS lobectomy done by skilled surgeons can be an option for more advanced disease. Abstract: Video-Assisted Thoracic Surgery (VATS) for treatment of lung cancer is being increasingly applied worldwide in the last few years. Since its introduction, many publications have been providing strong evidences that this minimally invasive approach is feasible, safe and oncologically efficient; offering to patients several advantages over traditional open thoracotomy, particularly for early-stage disease (I and II). The application of VATS for locally advanced disease treatment has also been largely described, but probably requires a further level of experience, which is more likely to be found in reference centers, with skilled experts. Although a large multi-institutional prospective randomized-controlled trial is the best way to confirm the superiority of one technique over another, such study comparing VATS versus open lobectomy for lung cancer is unlikely to ever come out. And in this scenario, retrospective data remains as the most reliable source of scientific information. Based on a literature review, the main objective of this article is to discuss to what extent VATS lobectomy can be considered the gold standard in the surgical treatment of lung cancer, taking into account the most important comparison aspects between the minimally invasive approach and open thoracotomy technique. This review addresses questions regarding lymph node dissection, oncologic efficacy, extended resections beyond standard lobectomy, post-operative complications/pain/quality of life, survival rates and the present limits of indication (and contraindication) for VATS, in order to define the real role of this technique on the surgical treatment of lung cancer in a minimally invasive, but safe and effective manner.